Deteksi Financial Statement Fraud dengan Fraud Diamond - Erna Hendrawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This research is motivated by concerns about the increasing cases of manipulation of financial statements that have the potential to undermine investor confidence and disrupt the stability of the financial sector. In this case, the Fraud Diamond approach  which includes four elements, namely foresight, opportunity, rationalization, and capability is used as a basis to identify indications of fraud in financial reporting. This study uses a quantitative approach with the object of research as many as 68 companies from the financial sector selected through purposive sampling techniques. The collected data was analyzed using multiple linear regression methods. The results of the analysis show that financial target and opportunity indicators have a significant influence in detecting the possibility of manipulation of financial statements. Meanwhile, financial stability, external pressures, rationalization, and individual abilities did not show a significant influence on fraud detection.